Pre-hospital National Early Warning Score (NEWS) is associated with in-hospital mortality and critical care unit admission: A cohort study. (March 2018) - Abbott, Tom E.F.; Cron, Nicholas; Vaid, Nidhi; Ip, Dorothy; Torrance, Hew D.T.; Emmanuel, Julian
Abstract: Background: National Early Warning Score (NEWS) is increasingly used in UK hospitals. However, there is only limited evidence to support the use of pre-hospital early warning scores. We hypothesised that pre-hospital NEWS was associated with death or critical care escalation within the first 48 h of hospital stay. Methods: Planned secondary analysis of a prospective cohort study at a single UK teaching hospital. Consecutive medical ward admissions over a 20-day period were included in the study. Data were collected from ambulance report forms, medical notes and electronic patient records. Pre-hospital NEWS was calculated retrospectively. The primary outcome was a composite of death or critical care unit escalation within 48 h of hospital admission. The secondary outcome was length of hospital stay. Results: 189 patients were included in the analysis. The median pre-hospital NEWS was 3 (IQR 1–5). 13 patients (6.9%) died or were escalated to the critical care unit within 48 h of hospital admission. Pre-hospital NEWS was associated with death or critical care unit escalation (OR, 1.25; 95% CI, 1.04–1.51; p = 0.02), but NEWS on admission to hospital was more strongly associated with this outcome (OR, 1.52; 95% CI, 1.18–1.97, p < 0.01). Neither was associated with hospital length of stay. Conclusion: Pre-hospital NEWS was associated with death or critical care unit escalation within 48 h of hospital admission. NEWS could be used by ambulance crews to assist in the early triage of patients requiring hospital treatment or rapid transport. Further cohort studies or trials in large samples are required before implementation. Highlights: NEWS has a growing dominance in UK hospitals but is not widely used in ambulances. NEWS calculated using ambulance observations is associated with in-hospital death and critical care unit admission. NEWS could be used by ambulance crews as an objective tool to triage patients with acute illness. A large scale trial should be carried out before widespread implementation of NEWS in ambulances. It is unclear if NEWS could be used by a call-taker or bystander to triage a patient before the ambulance arrives.